Multicomponent reactions driving the discovery and optimization of agents targeting central nervous system pathologies - Lucía Campos-Prieto; Aitor García-Rey; Eddy Sotelo; Ana Mallo-Abreu (Beilstein Journal of Organic Chemistry)
The ongoing quest to discover effective treatments for diseases remains a significant challenge for the scientific community. Multicomponent reactions (MCRs) have emerged as powerful tools in accelerating drug discovery, enabling the rapid generation of chemical libraries with high diversity in a time-efficient and environmentally sustainable manner. In this review, we focus on central nervous system (CNS) disorders, particularly Alzheimer's disease, Parkinson's disease, schizophrenia, depression, and epilepsy, where MCRs have contributed to the development of promising ligands in recent years. Rather than providing an exhaustive overview, this review aims to highlight key studies that address major CNS pathologies, relevant drug targets, and various MCR approaches. We have carefully selected representative articles and apologize to the authors whose important contributions may not be included. By concentrating on these pivotal studies, we strive to offer a clear and concise perspective on current research trends and breakthroughs in this field.